Issues of diagnostics and treatment of abdominal pain at irritable bowel syndrome at outpatient stage of the healthcare - Yu. A. Kucheryavy; T. L. Lapina; M. A. Livzan; M. F. Osipenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present the diagnostic and treatment algorithm for abdominal pain at out-patient/ polyclinic healthcare institutions and to demonstrate potential of hyoscine butylbromide application during diagnostic process and for relief of abdominal pain at irritable bowel syndrome.Summary. From 20% to 50% of all admissions to medical institutions are related to abdominal spasms and pain caused by irritable bowel syndrome (IBS). According to the Clinical guidelines of the Russian gastroenterological association and abdominal pain management algorithm at outpatient reception, the doctor on the basis of interviewing, inspection and physical data first of all should exclude acute abdominal diseases (acute pain, parietal pain) requiring urgent examination by the surgeon or gynecologist and subsequent hospitalization. In the case of visceral pain the minimal range of laboratory and instrumental tests is indicated. If the history of visceral pain is more than 6 months and there are no alarm symptoms, doctor should define specific features of clinical presentation already during outpatient visit, taking into account pain location, that provides formulation of preliminary diagnosis. Epigastric pain (dyspepsia), biliary pain, abdominal pain which can be accompanied by impaired frequency and consistency of stool determine the further investigation plan. Implementation of diagnostic algorithm allows to distinguish the organic disease or to establishthe diagnosis of functional disease. Hyoscine butylbromide at short-term treatment will relieve abdominal spasm as a symptomatic agent. Course treatment effectively reduces intensity and frequency of abdominal pain at IBS. The rate of adverse events and tolerability of hyoscine butylbromide are comparable to that of placebo.Conclusion. Symptomatic treatment by antispasmodic drugs is justified from the moment of referral for medical aid to outpatient department. Hyoscine butylbromide can be prescribed for relief of acute and chronic pain at any stage of diagnostic process. Course intake of antispasmodics has proved its efficacy for pain relief at IBS.